1997
DOI: 10.1080/02678379708256834
|View full text |Cite
|
Sign up to set email alerts
|

Power motivation, illness, coping strategies and psychological stress in police trainees

Abstract: Research suggests that there are substantial differences in the ways in which people cope with strcss, and that certain coping strategies buffer the degree of psychological and physical illness resulting from stress. Furthermore, personality, the situational contcxt and subjective appraisal of the situation are believed to mediate coping behaviour and its effectiveness. The present investigation reports the results of two studies of the relationship between coping behaviour and the personality disposition need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…More specifically, the findings show statistically significant results indicating that recruits reported using more emotion-focused, problem-focused, and seeking social support coping strategies early during academy training but reported using fewer of these strategies over the course of the seven-month training period at Time 2 and Time 3, each approximately three months apart. Langan-Fox et al (1997) found that police recruits reported the beginning phases of academy training as most stressful. The present findings may support these observations given that recruits reported using more coping strategies during this period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, the findings show statistically significant results indicating that recruits reported using more emotion-focused, problem-focused, and seeking social support coping strategies early during academy training but reported using fewer of these strategies over the course of the seven-month training period at Time 2 and Time 3, each approximately three months apart. Langan-Fox et al (1997) found that police recruits reported the beginning phases of academy training as most stressful. The present findings may support these observations given that recruits reported using more coping strategies during this period.…”
Section: Discussionmentioning
confidence: 99%
“…Langan-Fox et al. (1997) found that police recruits reported the beginning phases of academy training as most stressful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivation and stress measurement. Stress is regarded as an amorphous construct (Langan-Fox, 1996;Langan-Fox, Deery & van Vliet, 1997;Staal, 2004), which has been difficult to operationalize and measure. Researchers have claimed stress to be directly related to workload (Collet et al, 2009;Costa, 1995).…”
Section: Motivation and Stressmentioning
confidence: 99%
“…A promising stream of business and psychology research focuses on the link between individuals' motivational bases and their reaction to stressors (Kaplan et al, 2002;Langan-Fox, Deery, & Van Vliet, 1997), but theory-driven studies are nascent and empirical evidence is scant. Extending the research, we focus on a particular type of motivation and ask the following question: Does public service motivation (PSM) moderate the negative effects of workplace stressors on public employees' physical and mental wellbeing?…”
Section: Introductionmentioning
confidence: 99%